Social Entrepreneurship and Sustainable Development in Creating Value for Society and the Environment - Erlangga, Heri; Riani, Dini; Riadi, Farid; Hindarsah, Ida; Setiawati, Tita (Universitas Negeri Makassar, 2024)
Social entrepreneurship has emerged as a pivotal approach to addressing both societal and environmental challenges, integrating entrepreneurial principles with the goal of creating social and environmental value alongside economic sustainability. This paper explores the intersection of social entrepreneurship and sustainable development, examining how social entrepreneurs leverage innovation, resourcefulness, and business acumen to tackle complex issues such as poverty, inequality, environmental degradation, and climate change. By integrating the principles of sustainable development, social entrepreneurs aim to create ventures that promote long-term environmental stewardship and social equity. The study employs a qualitative approach, using in-depth interviews, participant observation, and document analysis to investigate the motivations, strategies, and challenges of social entrepreneurship. Key findings highlight the characteristics of social entrepreneurs, their contributions to the United Nations' Sustainable Development Goals (SDGs), and the systemic changes they foster. The paper also discusses the challenges faced by social entrepreneurs, such as access to funding and impact measurement, and identifies opportunities for growth through impact investing and technological advancements. The future of social entrepreneurship appears promising, with the potential for significant contributions to sustainable development through continued support and collaboration among stakeholders. The paper concludes by emphasizing the critical role of education, capacity-building, and multi-stakeholder partnerships in scaling the impact of social entrepreneurship.